1969
DOI: 10.1126/science.165.3890.277
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Lunar Surface in Mare Tranquillitatis

Abstract: More precise and comprehensive analytical results have been derived for lunar material at the Surveyor V landing site from alpha-scattering data. The composition is, in general, basaltic; the low sodium and high titanium contents, however, are distinctly different from the abundances in meteorites or common terrestrial rocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Several authors have suggested similarities with the basaltic achondrites, especially the eucrites. Turkevich et al (12) say, however, that in the lunar material "the high value for titanium and the relatively low value for iron are at variance with the content of these elements in eucrites and other calcium-rich achondrites." The statement about titanium is true, but that about iron is incorrect.…”
Section: Concentration Of Elements Atomicmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested similarities with the basaltic achondrites, especially the eucrites. Turkevich et al (12) say, however, that in the lunar material "the high value for titanium and the relatively low value for iron are at variance with the content of these elements in eucrites and other calcium-rich achondrites." The statement about titanium is true, but that about iron is incorrect.…”
Section: Concentration Of Elements Atomicmentioning
confidence: 99%
“…comment that Sinus Medii material may have lower titanium content than Mare Tranquillitatis material (12)], the sodium and potassium content is much lower, and the calcium content is higher than in lunar material. Also the points on the plot of CaO content as a function of Fe/ (Fe + Mg) (14) are in quite different positions (that for lunar material fitting well with eucrites).…”
Section: Concentration Of Elements Atomicmentioning
confidence: 99%
“…5 Values for the abundances of several radionuclides in eight lunar surface samples retturned by the Apollo I I mission have been reported by the Preliminary Examination Team (PET) (1). The preliminary nature of the experimental results was emphasized, and our conclusions must therefore necessarily be considered as tentative also.…”
mentioning
confidence: 99%
“…For example, the comparable specific radioactivities of 46Sc in lunar material and in stone meteorites presumably arise from the presence of the appreciable amount of titanium in the former (1,5), which compensates as target material for the lower iron abundance. The lower amount of 54Mn is probably due to the lower iron content in the Apollo 11 samples (the principal nuclear reactions leading to 54Mn, again, include iron as the target).…”
mentioning
confidence: 99%
“…The high titanium content (averaging 12% TiO2) of the basalts returned by the Apollo 11 mission was the greatest geochemical surprise of the first manned lunar landing, although it had been foreshadowed by the alpha-scattering data from the unmanned Surveyor V landing (TURKEVICH et al, 1969). Terrestrial basalts average about 2% Ti02 and very few contain as much as 5%.…”
mentioning
confidence: 99%